(untitled) (African Journal of Biomedical Research, 2022)
The Six-Minute Walk Test (6MWT) is a self-paced, inexpensive sub-maximal exercise test used as a reliable and valid measure of exercise capacity in children and adolescents. The American Thoracic Society has recommended establishment of specific reference values for Six-Minute Walk Distance (6MWD) for each population in various age groupings and ethnicities. However, limited information exists on reference values for different age groups in Nigeria. This study was designed to generate reference values for apparently healthy Nigerian children, aged 6-12 years. This cross-sectional study involving 334 apparently healthy Nigerian children was approved by the appropriate Health Research Ethics Committee. Their physical and selected physiological characteristics were measured and determined, as appropriate. Each participant had a single trial of the 6MWT and distance covered was recorded. Data were analysed using both descriptive and inferential statistics at p<0.05. Results showed the mean 6MWD of all participants was 504.38± 66.16m. The males had a significantly higher 6MWD. Age, weight and height, correlated significantly with the 6MWD. Prediction equations were derived from the physical characteristics of the children for 6MWD. Height and BMI were found to be significant predictors of 6MWD in all the participants. Percentiles and quartile deviations were also reported. The outcome of this study provided the reference value of 456m-506m for the Six-Minute Walk Distance among the apparently healthy Nigerian children aged 6 to 12 years. The prediction equation derived in this study has both clinical and field usefulness with regard to physical performance by children of this age range.